Interpersonal Relationships Among Black Couples and Depressive Symptoms During Pregnancy. Issue 5 (September 2018) - Caldwell, Cleopatra Howard; Misra, Dawn P.; Rogers, William B.; Young, Alford; Giurgescu, Carmen
Abstract: Objective: The purpose of this study was to examine associations of the mother–father relationship and social support with depressive symptoms during pregnancy among Black mothers and fathers. Methods: Fifty Black mother–father dyads from the Midwest completed a packet of questionnaires that included conflict with partner, social support, depressive symptoms, and sociodemographic characteristics. Results: Twenty-four percent of mothers and 16% of fathers had Center for Epidemiological Studies-Depression scores ≥23, which have been correlated with a major depression diagnosis. There were no differences in depressive symptoms between mothers and fathers. Fathers reporting high depressive symptoms were not more likely to be partnered with mothers reporting high depressive symptoms. Controlling for age, higher levels of conflict with partner, and lower levels of social support predicted higher levels of depressive symptoms for both mothers and fathers. Clinical Implications: Black expectant mothers and fathers may be at risk for clinical depression. Fathers experienced comparable levels of depressive symptoms with mothers, indicating the need to consider fathers' psychological adjustment during pregnancy. Higher levels of conflict with partner and lower levels of social support predicted higher levels of depressive symptoms for both parents. Maternal–child nurses should assess for mothers' as well as fathers' experiences of depressive symptoms and the mother–father relationship when providing prenatal care. Abstract : A significant number of Black mothers and fathers report depressive symptoms during pregnancy and postpartum. Based on the findings of this study and others, screening for depressive symptoms for all pregnant women and their partners has merit.